The association between urinary nitrate and prostate specific antigen without prostatic disease: a cohort study - Zhiyi Chen; Enpu Zhang; Lu Gan; Wenjuan Zhang; Guixiao Huang (BMC Urology)
Abstract Purpose The carcinogenic effects of nitrate reduction to nitrite are well established, and nitrate has been closely linked to various diseases. However, research on its effects on the urinary system remains limited, and its association with PSA remains unclear. This study aims to investigate the relationship between urinary nitrate and PSA. Methods We employed weighted generalized linear models, weighted univariate analysis, forest plots, weighted multivariable analysis, and generalized additive models (GAM) to investigate the relationship between urinary nitrate and PSA. Subgroup analyses were conducted to further validate the stability of this association across different groups. GAM was utilized to provide a more intuitive representation of the specific relationships between PSA and urinary nitrate. Results TPSA, FPSA, and the prostate specific antigen ratio (%, 4 ng/mL ≤ TPSA ≤ 10 ng/mL) showed negative correlations with urinary nitrate. After adjusting for confounders, only the prostate-specific antigen ratio maintained a significant negative association (β = -632.7; 95% CI: -1094.9, -170.6; P = 0.011), while correlations with TPSA and FPSA were not statistically significant. A nonlinear relationship was observed, where urinary nitrate initially remained stable or changed minimally before gradually declining. Conclusion This study identifies a negative correlation between urinary nitrate and the prostate-specific antigen ratio in individuals with gray-zone TPSA. These findings enhance our understanding of urinary nitrate’s impact and may help reduce overtreatment in this population.